"Ambidexterity": trump card for farm's innovativeness and competitiveness. Issue 13 (23rd December 2021) - Vecchio, Yari; Francescone, Martina; Adinolfi, Felice; De Rosa, Marcello
Abstract : Purpose: The paper aims to analyze the relevance of networking and social capital in promoting the adoption of sustainable innovation, then reinforcing trajectories of multifunctional agriculture. It puts forwards a systemic perspective by focusing on agricultural knowledge and innovation systems. More precisely, we share the idea of "micro agricultural knowledge and innovation systems", by addressing ambidexterity as engine for boosting sustainable innovation. Design/methodology/approach: Empirical analysis is focused on sustainable innovation adopted by young farmers in Italy and on the mediation effect of ambidextrous relations in performing innovation adoption. Ambidextrous relations are analyzed within at the micro-AKIS level, through the lens of social capital. Relationships between social capital and innovation adoption are statistically measured. Findings: The analysis shows how ambidexterity develops a mediation effect, with a strong impact on the farm's innovative capacity. Actually, our results confirm that ambidextrous relations reveal good performance and stimulate innovation and, consequently, farms' competitiveness, alongside the path of multifunctional agriculture. As a consequence, the relevance of networking activity in adoption of sustainable innovation may address possible policy action with the aim to strengthen ambidexterity and farm's innovativeness. Originality/value: The paper tries to fill a gap in literature, by focusing on micro-AKIS which are explored through the lens of social capital.